Acoustic emission behaviour during the evolution of a single pit on stainless steels. (1st May 2021) - Wu, Yunlong; Nong, Jing; Yuan, Sui; Guo, Qi; Xu, Jian
Highlights: AE behaviour of a single pit on stainless steels was investigated. A single pit on 17-4 PH is much more acoustically emissive than that on 304 SS. Hydrogen bubble can cause an AE signal when a pit is presented on metal surface. Perturbation of the electrolyte around a pit can cause the emission of AE signal. Abstract: The current study investigated the acoustic emission (AE) behaviour of a single pit evolution on two types of stainless steels using small-scaled electrodes. Dozens of AE signals were observed during pitting on 17-4 PH. However, 304 SS was much less acoustically emissive. According to the in-situ optical observation, black flocculent clusters were observed in 17-4 PH during pitting. However, such process was very weak in 304 SS. It was found that the hydrogen bubble formed inside the pit and the perturbation of electrolyte around the pit were able to create AE signals.